Eating and physical activity behaviours among ethnic groups in Queensland, Australia. Issue 11 (25th August 2020) - Gallegos, Danielle; Do, Hong; Gia To, Quyen; Vo, Brenda; Goris, Janny; Alraman, Hana
Abstract: Objective: To examine differences in eating and physical activity behaviours among ethnic groups in Queensland, Australia, and differences in those behaviours due to the duration of residency in Australia. Design: Cross-sectional study using baseline data collected for the Living Well Multicultural–Lifestyle Modification Program between October 2014 and June 2017. Setting: Culturally and linguistically diverse communities (CALD), including Afghani, Somali, Burmese, Pacific and South Sea Islander, Sri Lankan, Sudanese and Vietnamese, living in Queensland, Australia. Participants: People were recruited if they were ≥18 years old and living in the targeted CALD communities. Results: Burmese/Vietnamese, on average, had better eating scores in line with Australian dietary guidelines, compared with Afghani/Arabic-speaking (difference = 2·05 points, 95 % CI 1·39, 2·72), Somali/Sudanese (difference = 1·53 points, 95 % CI 0·79, 2·28) and Pacific Islander (difference = 1·46 points, 95 % CI 0·79, 2·13). Association between ethnicity and meeting the physical activity guideline was not significant. Those who stayed in Australia longer than a year were less likely to meet the physical activity guideline than those staying <1 year (OR = 0·51, 95 % CI 0·31, 0·84). There was no significant association between duration of residency in Australia and eating scores. Conclusions: Eating behaviours were significantly different among the ethnic groups in Queensland with Burmese/Vietnamese and Sri Lankan/Bhutanese having the healthiest diets. All ethnic groups were less likely to meet the physical activity guideline compared with the general Australian population. People with duration of residency of at least 1 year in Australia were less likely to meet the physical activity guideline compared with those who had shorter stays.